Interventions for mucous membrane pemphigoid and epidermolysis bullosa acquisita. - Kirtschig, G; Murrell, D; Wojnarowska, F; Khumalo, N (2003)
BACKGROUND: Mucous membrane pemphigoid and epidermolysis bullosa acquisita are acquired autoimmune blistering diseases of the skin. Although they are rare, both can result in scarring of mucous membranes, which may lead to blindness and life threatening respiratory complications. OBJECTIVES: To assess the effects of treatments for mucous membrane pemphigoid and epidermolysis bullosa acquisita. SEARCH STRATEGY: Randomised Controlled Trials (RCTs) of patients with MMP or EBA were identified from MEDLINE and EMBASE from their inception to March 2000. The Cochrane Skin Group Specialised Register and the Cochrane Controlled Trials Register (CCTR) were last examined in February 2002. The bibliographies from identified studies were searched. The author who has conducted clinical trials in the field was contacted to identify unpublished trials. SELECTION CRITERIA: RCTs involving participants of any ages, and with a diagnosis confirmed by immunofluorescence. Where no RCTs were located, studies with other designs were considered. DATA COLLECTION AND ANALYSIS: Data were extracted from all included studies using a defined electronic data extraction protocol. Two reviewers evaluated the studies in terms of the inclusion criteria. The data from identified RCTs was extracted independently by three reviewers and subsequently checked for discrepancies. Any disagreements were resolved by discussion with each other and the fourth reviewer. Meta-analysis was not appropriate due to a lack of data. MAIN RESULTS: We found two small RCTs of MMP, both conducted in patients with severe eye involvement. The same author conducted both trials. In the first trial cyclophosphamide was superior to prednisone after six months of treatment; all 12 patients responded well to cyclophosphamide versus a good response in only five of 12 patients treated with prednisone (relative risk 2.40, 95% confidence interval 1.23 to 4.69). In the second trial all 20 patients treated with cyclophosphamide responded well to it after three months of treatment, but only 14 of 20 patients responded to the treatment with dapsone (relative risk 1.4, 95% confidence interval 1.07 to 1.90). We were not able to identify a RCT of therapeutic interventions in EBA. Thirty reports of uncontrolled studies of treatment for MMP involving five or more patients and 11 reports of treatment for EBA involving two or more patients were found, but were difficult to interpret. REVIEWER'S CONCLUSIONS: There is limited evidence (from two small trials) that severe ocular mucous membrane pemphigoid responds best to treatment with cyclophosphamide combined with corticosteroids, and that mild to moderate disease in most patients seems effectively suppressed by treatment with dapsone. It is difficult to make any treatment recommendations for EBA in the absence of reliable evidence sources.